Legal Protection for Children as Victims of Trafficking in Persons - Nursariani Simatupang; Faisal Faisal (International Journal Reglement & Society (IJRS), 2023)
Trafficking of children is an act that takes away the human rights of children. Trafficking in children seizes children's freedom, destroys the period of growth and development of children. Child trafficking is closely related to solicitation and persuasion from perpetrators. On the other hand, child trafficking is also accompanied by acts of coercion and violence by actors against children. As victims of trafficking in persons, children are unable to fight back, both physically and mentally. Children experience helplessness that can damage their future. For this reason, it is necessary to provide legal protection for children as victims of trafficking in persons. The legal protection provided is in the form of punishment for perpetrators of child trafficking. The legal protection provided aims to ensure that children are guaranteed security, peace and prosperity during their growth and development period, so that children are able to become the next generation of the nation and become leaders of the nation in the future